Expert recommendations and clinical considerations in the use of onasemnogene abeparvovec gene therapy for spinal muscular atrophy. Issue 4 (20th July 2021) - Kichula, Elizabeth A.; Proud, Crystal M.; Farrar, Michelle A.; Kwon, Jennifer M.; Saito, Kayoko; Desguerre, Isabelle; McMillan, Hugh J.
Abstract: Spinal muscular atrophy (SMA) is an autosomal recessive, neurodegenerative disease caused by biallelic mutations in the survival motor neuron 1 ( SMN1 ) gene. SMA is characterized by motor neuron degeneration, resulting in progressive muscle atrophy and weakness. Before the emergence of disease‐modifying therapies, children with the most severe form of SMA would never achieve the ability to sit independently. Only 8% survived beyond 20 months of age without permanent ventilator support. One such therapy, onasemnogene abeparvovec, an adeno‐associated virus–based gene replacement therapy, delivers functional human SMN through a one‐time intravenous infusion. In addition to substantially improving survival, onasemnogene abeparvovec was found to increase motor milestone attainment and reduce the need for respiratory or nutritional support in many patients. This expert opinion provides recommendations and practical considerations on the patient‐centered decisions to use onasemnogene abeparvovec. Recommendations include the need for patient‐centered multidisciplinary care and patient selection to identify those with underlying medical conditions or active infections to reduce risks. We also describe the importance of retesting patients with elevated anti–adeno‐associated virus serotype 9 antibodies. Recommendations for prednisolone tapering and monitoring for potential adverse events, including hepatotoxicity and thrombotic microangiopathy, are described. The need for caregiver education on managing day‐to‐day care at time of treatment and patient‐ and family‐centered discussions on realistic expectations are also recommended. We detail the importance of following standard‐of‐care guidance and long‐term monitoring of all children with SMA who have received one or more disease‐modifying therapy using registries. We also highlight the need for presymptomatic or early symptomatic treatment of this disorder.